Community Education Vulnerability in Concessions of Siulak Mukai District Kerinci Regency - Fitria, Rahma (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The purpose of this study is about the vulnerability of education in concessions. This research combination research that combines quantitative methods with qualitative methods. The subjects to be studied are school age children and parents of school-age children in concessions. The sample is defined by proportional techniques in the school-ag population at each level of education. The sub-distric is the low motivation of individuals, parents, cultural environments that are less concerned with education and low accessibility to schools.